علم مقاصد شريعت كى اہميت، اہل فن كى خدمات، حدود اور شرائط - Dr. Fazail Asrar Ahmad; Dr. Inam al-Rehman; Abdul Wahab (الآفاق اسلامی و تحقیقی مجلہ)
No ruling of shari'ah is devoid of purpose, whether we can reach it or not, it has been explained in many books in previous periods, but it did not exist in the form of a particular art, first of all, Imam Abu Ishaq Shatabi regularly allocated a part of his book to it and did the basic technical discussions that could be held regarding the objectives. Knowledge has become a regular art form and this knowledge is very important for the solution of fiqh and to satisfy the scientific minds of the modern era. This research aims to describe the importance of maqāshid sharia services of scholars, its limits, and conditions. The study begins by explaining the meaning of ijtihād as well as maqashid sharia, and finally discovering the use of maqāshid sharia on the contemporary fatwas. The approach used in this research is descriptive-qualitative approach, because this study is intended to reveal and describe the meaning of ijtihād as well as maqāshid sharia, and the use of maqāshid sharia, it can be concluded that the maqāshid sharia have an important role in ijtihād. Therefore, the contemporary scholars relay on the maqashid sharia in their fatwas; in worship, transactions, family jurisprudence.